MI (2‐methyl‐4‐isothiazolin‐3‐one) contained in detergents is not detectable in machine washed textiles. Issue 1 (5th January 2018) - Hofmann, Maja A.; Giménez‐Arnau, Ana; Aberer, Werner; Bindslev‐Jensen, Carsten; Zuberbier, Torsten
Abstract: Background: European legislation has banned the preservative methylisothiazolinone (MI) from inclusion in leave‐on cosmetics. However, the risk for allergic reactions depends on exposure. The aim of this study was to determine the risk of MI in laundry detergents for household machine washing. Methods: Different formulations of laundry detergents with commercial MI levels, up to one thousand ppm were used and three different types of clothes were washed in a normal household machine setting one time and 10 times. The level of MI was measured by HPLC. Results: While MI could be retrieved in the positive control of clothes drenched with washing powder but not washed afterwards, MI could not be detected in any specimen of clothes washed under household conditions. The detection limit was 0.5 ppm. Conclusion: It is important to discuss the difference of risk and hazard. While MI clearly is a high hazard as a strong contact allergen, the risk depends on exposure. Regarding the risk of exposure levels for the consumer to MI in clothes it can be stated that the use of MI in laundry detergents is safe for the consumer if these products are used according to the instructions in the normal household setting machine wash.